Boron Nitride FIlms: Desolvation‐Triggered Versatile Transfer‐Printing of Pure BN Films with Thermal–Optical Dual Functionality (Adv. Mater. 38/2020). Issue 38 (21st September 2020) - Han, Yujin; Han, Hyeuk Jin; Rah, Yoonhyuk; Kim, Cheolgyu; Kim, Moohyum; Lim, Hunhee; Ahn, Kwang Ho; Jang, Hanhwi; Yu, Kyoungsik; Kim, Taek‐Soo; Cho, Eugene N.; Jung, Yeon Sik
Abstract : In article number 2002099, Eugene N. Cho, Yeon Sik Jung, and co‐workers develop a new approach to printing pure BN films with highly compact and aligned architectures based on desolvation‐induced interfacial adhesion switching. The binder‐free BN films achieve both high thermal conductivity and optical transparency, demonstrating the multifunctionality of thermal management and optical enhancement for a variety of optoelectronic devices.